Myiasis pada Ruminansia: Diagnosis, Manajemen Terapi dan Pencegahan: Myiasis in ruminants: Diagnosis, Therapy andPrevention Management - Yanuartono Kaswardjono; Soedarmanto Indarjulianto; Alfarisa Nururrozi; Hary Purnamaningsih (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2019)
Myiasis is defined as a condition in which maggots are from certain fly species that utilize living, dead, or necrotic tissue from the host as a feed source for their growth and development and attack all types of vertebrate animals that are warm-blooded including humans. myiasis is often found in domestic animals in tropical regions throughout the world, especially in developing countries such as Indonesia and is generally associated with low levels of welfare of farmers. The diagnosis of myiasis is based on a clinical examination of wound bleeding, fever, a characteristic odor, the discovery of exudates and maggots in the wound. Myiasis treatment is generally local followed by manual removal of larvae and necrotic tissue debris. Systemic treatment usually uses broad-spectrum antibiotics especially when secondary infections occur. Disease prevention can be done by providing information to farmers to pay attention to and carry out livestock sanitation, pens, the surrounding environment and control flies using various methods. Keywords: clinical examination, disease prevention, maggot, myiasis